Hiatus Hernia in Adult and Children: Case Report - Hanifa Fathinatul Amirahayu; Yuyun Yueniwati (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2026)
Introduction: Diaphragmatic and hiatal hernias are clinically significant and may lead to serious complications if not promptly recognized and treated. Differentiating these entities on imaging can be particularly challenging when extensive visceral herniation distorts normal anatomical landmarks. Case Presentation: We report two rare cases illustrating distinct diagnostic challenges. The first involved a 49‑year‑old woman with paraesophageal hernia complicated by gastric volvulus. The second concerned a 1‑year‑old girl initially misdiagnosed with Bochdalek hernia, later identified intraoperatively as type III hiatal hernia, an unusual presentation in infancy. Results: Radiologic imaging was crucial for diagnosis and management. Contrast‑enhanced CT offered precise anatomical detail, enabling accurate identification of hernia type, extent, and complications, thereby guiding surgical planning. Notably, in the pediatric case, CT contributed to distinguishing a rare type III hiatal hernia from an initial Bochdalek diagnosis Conclusion: These cases emphasize the key role of CT in distinguishing hiatal from congenital diaphragmatic hernias. Understanding hernia anatomy and imaging features is vital for timely diagnosis, surgical planning, and preventing serious complications.